Adaptive neural controller for attitude stabilization of quadrotor unmanned aerial vehicle (UAV) - Shaiful Zairi Ahmad Subhi (School of Mechatronic Engineering, 2012)
This thesis also will present the development of an UAV that uses a new concept named quadrotor which are a combination of helicopter and airplane.